Silencing Anxiety with Social Savvy: The Role of Interpersonal Intelligence in EFL Classrooms - Hidayat, Cece; Suherman, Maman; Gaffar, Muhammad Andriana; Siti Kania Febriyanti; Nenden Ismaurah (VELES Voices of English Language Education Society, 2024)
Communication anxiety significantly hinders learning outcomes in English as a Foreign Language (EFL) classrooms. This research explores the correlation between interpersonal intelligence and communication anxiety among high school students, assessing how variations in interpersonal skills influence anxiety levels during EFL interactions. Employing a quantitative approach, the study engaged 32 eleventh-grade students from class 11 MIPA 3 at SMA Mekar Arum, selected through random sampling. Data were collected using designed questionnaires to evaluate interpersonal intelligence and communication anxiety and analyzed with Pearson Product Moment Correlation via SPSS 22.0. The results indicated a significant negative correlation between interpersonal intelligence and communication anxiety (r= -0.494, p < 0.05), demonstrating that students with higher interpersonal intelligence experience lower communication anxiety. Notably, 65.6% of the students demonstrated medium levels of interpersonal intelligence, while 34.4% had high levels. In terms of communication anxiety, 56.3% of students experienced moderate levels, and 43.8% experienced high levels. Conclusively, this study underscores the importance of fostering interpersonal intelligence as a strategic approach to alleviate communication anxiety in EFL settings. It recommends that EFL instructors integrate group-based and interactive activities that enhance interpersonal relations among students to improve their educational experience and outcomes.